Analisis Pemanfaatan dan Dampak Teknologi Internet dalam Meningkatkan Daya Saing Usaha E-Bisnis - Sri Anggraini; Tri Damaiyanti; Maya Rafika Utami; Eko Prasetyo; Nurbaiti Nurbaiti (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to analyze the role of internet technology in enhancing the competitiveness of ebusiness in Indonesia, particularly in the sector of small and medium enterprises (SMEs). Based on theoretical reviews, internet technology, e-business, technology adoption (TAM), and the concept of competitiveness serve as the main foundations for understanding the ongoing digital transformation. The research employed a descriptive qualitative method with a purposive sampling technique, involving five informants consisting of digital SME owners, online store managers, and users of service platforms. Data were collected through interviews and observations, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the internet plays a crucial role as an essential infrastructure that enhances marketing effectiveness, expands market reach, and improves operational efficiency. Marketplaces, social media, and delivery-service platforms contribute significantly to sales growth and service quality. However, challenges such as low digital literacy, platform commission fees, changes in social media algorithms, and uneven infrastructure development still limit optimal utilization. From a policy perspective, the study recommends strengthening digital infrastructure and improving national digital literacy. This research emphasizes that the success of e-business depends on technology access, human resource competence, and support through public policy. It can be concluded that internet technology serves as a vital foundation for e-business competitiveness in the digital era.